2015
DOI: 10.1101/gad.257840.114
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation restrains transposons from adopting a chromatin signature permissive for meiotic recombination

Abstract: DNA methylation is essential for protecting the mammalian germline against transposons. When DNA methylation-based transposon control is defective, meiotic chromosome pairing is consistently impaired during spermatogenesis: How and why meiosis is vulnerable to transposon activity is unknown. Using two DNA methylationdeficient backgrounds, the Dnmt3L and Miwi2 mutant mice, we reveal that DNA methylation is largely dispensable for silencing transposons before meiosis onset. After this, it becomes crucial to back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
137
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(156 citation statements)
references
References 73 publications
9
137
0
Order By: Relevance
“…The pattern of H3K27me3 is especially interesting because it is occasionally symmetrical on each side of the SC, which hints at an association with defined regions of the genome (33). These clusters may be selected to escape recombination, similar to how DNA methylation was suggested to prevent recombination in transposon sequences (34). Another possible hypothesis is that H3K27me3 clusters may be involved in the formation of the SC itself (35).…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of H3K27me3 is especially interesting because it is occasionally symmetrical on each side of the SC, which hints at an association with defined regions of the genome (33). These clusters may be selected to escape recombination, similar to how DNA methylation was suggested to prevent recombination in transposon sequences (34). Another possible hypothesis is that H3K27me3 clusters may be involved in the formation of the SC itself (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, the sheer abundance of preexisting L1 copies in the mouse genome presents a formidable technical challenge to quantifying the frequency and magnitude of de novo insertions. Indeed, this technical barrier has prevented the characterization of the extent and timing of retrotransposition during germ-cell development (22). For example, even the most rudimentary information is unavailable as to what extent retrotransposition occurs in piRNA pathway mutants and whether an increase of insertions, if any, is concurrent with the meiotic phenotype.…”
Section: Significancementioning
confidence: 99%
“…The negative impact of LTR transposons on recombination in wheat could also be attributed to their associated epigenetic patterns which condense DNA and lock the regions, preventing their accessibility to the recombination machinery. As an example, in mouse, methylation leads to DNA conformation which prevents transposons from adopting a permissive chromatin structure for meiotic recombination (Zamudio et al 2015). Finally, in barley, pericentromeric regions with low recombination rates bear LTR retrotransposons that carry the epigenetic landmarks H3K9me2 and H3K27me1 which establish a constitutive heterochromatic state (Baker et al 2015).…”
Section: Retrotransposons Associate With Reduced Recombination Ratementioning
confidence: 99%
“…In Arabidopsis, DNA methylation can silence CO hotspots and plays an essential role in forming domains of meiotic recombination along chromosomes (Yelina et al 2015). Recently, a study in mouse revealed that DNA methylation can prevent transposons from adopting chromatin characteristics amenable to meiotic recombination (Zamudio et al 2015), underlying the importance of DNA conformation and the likely role of epigenetic marks on recombination.…”
mentioning
confidence: 99%